Assessing the impact of dietary habits on health-related quality of life requires contextual measurement tools - Ruano-Rodríguez, Cristina; Serra-Majem, Lluis; Dubois, Dominique (Frontiers in Pharmacology, 2015)
The increase of non-communicable diseases at all ages has fostered the general concern for sustaining population health worldwide. Unhealthy lifestyles and dietary habits impacting physical and psycho-social health are well known risk factors for developing life threatening diseases. Identifying the determinants of quality of life is an important task from a Public Health perspective. Consumer-Reported Outcome measures of health-related quality of life are becoming increasingly necessary and relevant in the field of nutrition. However, quality of life questionnaires are seldom used in the nutrition field. We conducted a scientific literature search to find out the questionnaires used to determine the association between dietary habits and quality of life. A total of 13 studies were eligible for inclusion. Across these studies the Short Form–36, a generic (nondisease-specific) health-related quality of life measurement instrument was the most widely used. However, generic measures may have limited content validity in the context of dietary habits interventions. We recommend additional contextual diet-specific health-related quality of life measures are also needed for evaluating the impact of diet habits on daily life functioning and well-being.